Kajian Aktivitas Indeks Glikemik Brownies Kukus Substitusi Tepung Ubi Jalar Termodifikasi - Putri, Sefanadia (Politeknik Kesehatan Tanjungkarang, 2017)
Sweet potato is a source of carbohydrates with a low glycemic index. That could aimed to substitute wheat flour in making brownies. These study purposes were to determine the organoleptic characterictic, glycemic index and glycemic load of Modified sweet potato Flour. It was an experimental laboratory research with true design-experiment. The experiment was arranged in a randomized complete block design (RCBD) with four replications. There were 5 formula, that were ratio of modified sweet potato flour to wheat flour 0: 100 (F1), 25: 75 (F2), 50: 50 (F3), 75: 25 (F4) and 100: 0 (F5). It was to get a product that could be accepted by organoleptic tests, brownies products were most preferred. The most preferred brownies was tested the glycemic index and glycemic load. Statistical analysis showed that the concentration of modified sweet potato flour were not significantly affected the color, flavor, aroma and texture, but significant effected on the overall acceptance of brownies. Formula 3 was the most preferred modified sweet potato flour ratio. Glycemic index and glycemic load test of the most preferred formula were 53.76% (lower) and 19.15%, respectively.